2022
DOI: 10.36341/psi.v5i2.2134
|View full text |Cite
|
Sign up to set email alerts
|

Kesehatan Mental Siswa SMP-SMA Indonesia Selama Masa Pandemi dan Faktor Penyebabnya

Abstract: Kesehatan mental pada remaja merupakan permasalahan penting yang perlu diperhatikan. Pandemi COVID-19 membuat permasalahan ini menjadi semakin perlu mendapatkan perhatian serius dari para pemangku kepentingan, terutama terkait dengan implementasi kebijakan Pembelajaran Jarak Jauh (PJJ). Hasil penelitian sebelumnya menunjukkan adanya sejumlah keluhan dari siswa terkait pelaksanaan PJJ. Oleh karena itu penelitian ini dilakukan dengan tujuan untuk memberikan gambaran deskriptif tingkat depresi dan kecemasan pada … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0
6

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 8 publications
0
2
0
6
Order By: Relevance
“…According to the previous research, students of the junior high schools and the senior high schools in Indonesia suffered mental and emotional problems during the pandemic (Addini et al, 2022). National Survey on Indonesian Teenager's Mental Health of 2022 shows that 15.5 million of the teenagers (34.9%) experienced mental health issues in the last 12 months and 2.45 million of the teenagers (5.5%) experienced mental issues in the last 12 months.…”
Section: Discussionmentioning
confidence: 99%
“…According to the previous research, students of the junior high schools and the senior high schools in Indonesia suffered mental and emotional problems during the pandemic (Addini et al, 2022). National Survey on Indonesian Teenager's Mental Health of 2022 shows that 15.5 million of the teenagers (34.9%) experienced mental health issues in the last 12 months and 2.45 million of the teenagers (5.5%) experienced mental issues in the last 12 months.…”
Section: Discussionmentioning
confidence: 99%
“…Implementasi tindakan pengendalian kedaruratan kesehatan masyarakat memiliki dampak besar pada psikologi siswa remaja. Akibat negatif dari pandemi COVID-19 merambah ke segala aspek masyarakat, tidak hanya kesehatan tetapi juga ekonomi, pendidikan, agama, dan politik (Addini et al, 2022). Efek psikologis negatif diperkirakan akan terjadi dan memburuk ketika anak-anak dikurung di rumah mereka tanpa adanya kegiatan di luar ruangan dan komunikasi interpersonal dengan teman-teman yang seusia.…”
Section: Pembahasanunclassified
“…Namun, pendidikan online membutuhkan pemikiran, desain, dan implementasi yang sistematis. Tetapi pada keadaan yang mendesak ini terutama Indonesia sebagai episentrum pertama, tidak ada persiapan yang matang, dan format e-learning dapat sangat bervariasi antar daerah dan sekolah yang berbeda (Addini et al, 2022). Oleh karena itu, kami hanya bisa melakukan penilaian umum.…”
Section: Pembahasanunclassified
See 1 more Smart Citation
“…As for previous research, it was stated that many adolescents experienced mental health problems. During the pandemic, the mental health of Indonesian Middle School and High School students showed that 46% of students experienced symptoms of anxiety and 56% experienced symptoms of depression (Addini, S., E., et al, 2022). Meanwhile, the mental health condition of junior high school adolescents in Pekanbaru showed that as many as 78 people (36.1%) teenagers experienced an abnormal mental-emotional condition, as many as 76 people (35.2%) teenagers with a normal mental-emotional condition, and as many as 62 people ( 28.7%) adolescents experience mental emotional conditions in the borderline category (Malfasari, E., et al, 2020).…”
Section: Introductionmentioning
confidence: 99%